PENGARUH KELENGKAPAN FASILITAS, ADMINISTRASI KESEHATAN DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT INAP DI RUMAH SAKIT PRATAMA KRIOPANTING KABUPATEN BANGKA SELATAN - Wulandari Wulandari; Afrizal Afrizal; Fithriawan Nugroho; Efendi Efendi (LPPM STIE PERTIBA Pangkalpinang, 2023)
This study aims to determine the influence of facility completeness, health administration, and service quality on inpatient satisfaction at the Pratama Kriopanting Hospital. This research is a quantitative study, so the data collection that will be used in this study is done using a questionnaire that will be filled out directly by respondents. This study utilizes multiple linear regression analysis, the results of which indicate that the variables of facility completeness, health administration, and service quality affect inpatient satisfaction at the Pratama Kriopanting Hospital in the Payung Sub-district. The results of the t-test show that the variables of facility completeness, health administration, and service quality obtain a significance value of <0.05. The results of the F-test show that the variables of facility completeness, health administration, and service quality collectively have a positive influence on inpatient satisfaction at the Pratama Kriopanting Hospital in the Payung Sub-district. The coefficient of determination (R-Square) indicates that facility completeness, health administration, and service quality influence inpatient satisfaction by 51.3%, while the remaining 48.7% is explained by other variables outside the scope of this research.